Determinants of the capital structure of TSL sector enterprises - Jędrzejczak-Gas Janina (Management, 2018)
Determinants of the capital structure of TSL (Transport, Spedition, Logistics) sector enterprises The capital structure has been of interest for researchers in the field of financial theory for over 60 years. However, literature surveys show that relatively few studies on the structure of capital and the factors shaping it can be applied to the TSL industry. The TSL (Transport, Spedition, Logistics) sector belongs to industries with a high development potential, both in the world and Poland. In order to meet the need for the diagnosis of the TSL industry in Poland, the research was undertaken to identify and examine the strength and direction of the impact of selected factors on the capital structure of enterprises in the TFL sector in Poland. The article consists of two parts. The first part explains the issues related to defining the concept of capital structure and includes identification of capital structure determinants based on the literature. The second part shows research methods, describes the sample, defines variables and presents results of the research. The enterprises listed on the NewConnect market were the subject of the research. It was to achieve the set goal that the correlation analysis and the linear regression method were used. Both correlation analysis and regression analysis have not confirmed the significance of all seven capital structure determinants. The correlation analysis has confirmed the significance of four determinants: asset structure, profitability, company size and financial liquidity. The regression analysis has also confirmed the statistical significance of the four determinants; these are: the structure of assets, size of the company, financial liquidity and the effective tax rate. The analysis of correlation shows that the level of indebtedness is positively correlated with the size of the enterprise and profitability, while negatively, with the structure of assets and financial liquidity. In turn, the regression analysis shows that the level of indebtedness is positively correlated only with one variable: the size of the enterprise, while negatively with the three variables: the structure of assets, financial liquidity and the effective tax rate.